Quantum structural studies : classical emergence from the quantum level - Kastner, Ruth E., 1955-; Jeknic-Dugic, Jasmina; Jaroszkiewicz, George (Hackensack, NJ : World Scientific, 2017)
'The structural aspects of composite quantum systems in the foundation, interpretation and application of quantum theory is an increasingly prominent topic of physics research. As an emerging field, it seeks to understand the origins of the classical world of experience from the quantum level. Quantum Structural Studies presents conceptual fundamentals and mathematical methods for investigating the structuring of quantum systems into subsystems. Split into four sections, the topics covered include the historical and philosophical aspects of quantum structures, specific interpretive approaches and ontologies, and alternative methodological approaches to quantum mechanics. Questions addressed are: Can the classically relevant degrees of freedom (such as the center of mass) be considered physically realistic, and if so, in what sense? In what sense might various emergent structures be relevant for the transition from the quantum description to the classical? Do suggested new approaches describe phenomenology and proposals for new experiments? Specialists, graduate students and researchers seeking an introduction to the field of emergent structures and new directions for research and experimentation can use this book to find up-to-date representative texts and reviews'--
Bohr's diaphragms / T. Bai, J. Stachel --'It ain't necessarily so': interpretations and misinterpretations of quantum theory / J. Stachel -- Beyond complementarity / R.E. Kastner -- Representational realism, closed theories and the quantum to classical limit / C. De Ronde -- Principles of empirical science and the interpretation of quantum mechanics / G. Jaroszkiewicz -- Primitive ontology and the classical world / V. Allori -- Fluidodynamic representation and quantum jumps / L. Chiatti & I. Licata -- Relativity and (quantum-) electrodynamics from (onto-) logic of time / C. Baumgarten -- The quantum state as displacement / P.R. Holland -- Symmetry and natural quantum structures for three-particles in one-dimension / N.L. Harshman -- Quantum to classical transitions via weak measurements / E. Cohen -- Bound states as fundamental structures / R.E. Kastner -- A top-down view of the classical limit of quantum mechanics / S. Fortin, O. Lombardi -- A top-down versus a bottom-up hidden-variables description of the Stern-Gerlach experiment / M. Arsenijevi{u28EC} J. Jekni{u28ED}Dugi{u28E0}& M. Dugi{u28EE}
Includes bibliographical references and index.
Keywords: Quantum systems; Quantum theory; Degree of freedom; Atomic structure